Optimization of the attention of OPEX and CAPEX projects through the implementation of an integrated project management system SIGPRO, in 2015. - Málaga Enciso, Erik Robin (2017)
The demand for development and execution of infrastructure projects in the Superintendency of Plant Engineering has increased over the years without the organizational structure or management methods have undergone substantial changes. The effectiveness of the implementation of an Integrated Project Management System in the Planning and Technical Services Management that optimized the attention of Opex projects and the Southern Peru Copper Corporation was measured. Methodology: Experimental operational research in the field of project management. Results: The project management model of Cuajone Plant Engineering allows the agilization in the attention of the same under the methodological approach of the PMI (Project ManagementInstitute). lt is possible to cover Project Management and Document Management allowing to improve efficiency from the reduction of time and costs to the fulfillment of the scope of the same. Conclusion: The implementation of the SIGPRO management system in 2015 in the area of Cuajone Plant Engineering generates the greatest variation in project attention compared to the last 14 years, resulting in a total variation of US $ 18,130,000 representing an increase of 78.32% compared to 2014. In addition, the highest project attention was recorded in 2015, with a total of US $ 41,200,000.